Marketing analysis of JJK Jyväskylä, a first division football club in Finland - Szeróvay, Mihály (2010)
ABSTRACT Master’s Thesis, 78 pages, 3 appendices Sport Marketing 2010 This empirical case study investigated a First Division semi-professional football club in Finland and tried to explore interrelationships between factors that affect the marketing activities of the club. Previous research shows controversial results about how the on-field performance of a team, attendance and marketing opportunities are interconnected, which underpins the relevance of the present work. In addition, emphasis was also put on ascertaining the antecedents and level of fan satisfaction and identification towards the team, as well as discovering the relationship between them. Furthermore, the research was aimed at detecting a presumed correlation between identification of fans, and their sensitivity to the result of the games. Likewise, an attempt was made to find out whether increasing fan satisfaction or fan identification indicates higher sponsor awareness. In order to successfully implement the study, an on-line survey, interviews, and participant observation was utilised, as well as statistical data obtained from Football Club JJK Jyväskylä. With the analysis of the collected data, this study has found that improving onfield performance triggers higher attendance and further opportunities in marketing. In addition, there is an existing relationship between factors that determine fan satisfaction and fan identification. Beside these, it has been concluded that JJK fans’ sponsor awareness and attitude stand at a low level, therefore JJK’s sponsorship strategy needs to be reorganised. Finally, it has been revealed that highly satisfied and identified fans are more eager to buy a season ticket for the following season and recommendations were made how to establish and strengthen the JJK brand. Implementing the results of this work could help enhance the quality of marketing management and raise the level of services provided to supporters and sponsors of the club. Similarly, this topic area was performed under specific conditions related to Finland.